INTERNAL OVERSIGHT, TRANSPARENCY, AND INSPECTORATE EFFECTIVENESS: EVIDENCE FROM THE MONITORING CENTER FOR PREVENTION (MCP) IN MALUKU PROVINCE - Rizal; Aminah Bahasoan; Hendry Selanno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the extent to which internal oversight and administrative transparency influence the effectiveness of the Maluku Provincial Inspectorate in supporting the achievement of the Monitoring Center for Prevention (MCP) program. Strengthening internal control systems and improving transparency is crucial for ensuring accountable governance and preventing administrative irregularities. Using a quantitative associative design, the study surveyed 105 Inspectorate personnel through structured Likert-scale questionnaires. Data were analyzed using instrument validity tests, reliability tests, classical assumption testing, and multiple linear regression. The results show that internal oversight has a strong and significant positive effect on Inspectorate effectiveness, demonstrating its central role in improving compliance, minimizing risks, and supporting MCP performance. Administrative transparency also exerts a significant positive influence, although to a lesser degree, indicating that accessible information systems and open documentation enhance monitoring accuracy. Simultaneously, both variables significantly predict Inspectorate effectiveness, confirming the importance of integrated internal control and transparency frameworks. This study contributes empirical evidence to public governance research and highlights the need to reinforce control mechanisms and transparency practices to improve MCP achievements in regional government institutions.